The effect of various physical parameters on the size and shape of necrosed tissue volume during ultrasound surgery - Hynynen, K.; Damianou, Christakis A. (My University, 1994)
The purpose of this study was to test the concept of using calculated thermal dose as a predictor for the necrosed tissue volume. A parametric study was conducted where the sonication parameters (pulse duration, power), transducer parameters (frequency, F number) and tissue properties (perfusion rate, attenuation) were varied and their effect on the lesion size was investigated. In vivo experiments where a focused ultrasound beam was used to induce tissue necrosis in thigh muscle of dog and rabbit were also conducted to obtain the reliability of the predictions. The experimental and simulated lesion sizes compared well. From the parametric study the threshold intensity for 1- and 5-s sonications were found to be about 1000 and 400 W/cm, respectively. It was found that the lesion size was practically perfusion independent for pulses 5 s or shorter. The lesion size increases with increased pulse duration, acoustical power, and F number, but decreases with increased frequency provided that the focal intensity is kept constant. It was found also that the deeper the focus is in the tissue, the smaller the frequency range that causes selective tissue necrosis in the focal zone. © 1994, Acoustical Society of America. All rights reserved.
Keywords: Musculoskeletal system; Lesion; Necrosis; Optical imaging; Ultrasound; Sonochemistry; Acoustics